Consumer Protection Against Standard Clauses in Business Transactions Through E-Commerce - Aditya Migi Prematura; Suryani Suryani; Agung Aditya (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2022)
Standard agreements or standard agreements aim to provide convenience or practicality for the parties in conducting transactions, especially in the business sector. Problems will arise when consumers in electronic business transactions face standard agreement formulas in which many standard clauses require consumers to agree. In practice, currently, no e-commerce platform does not use standard agreement formats and clauses in transactions with consumers. This form of the agreement positions the consumer as a party that has no bargaining power, so whatever the contents of the standard agreement are, inevitably must be agreed upon, even though basically the consumer knows that the contents of the agreement are burdensome to him. The problem under study is how is the legal protection of consumers involved in standard agreements with the exoneration clause in a business transaction through electronic media (e-commerce). The research method used is a normative legal research method with a statute approach, a conceptual approach, and the views of experts related to the problem. The results of the study show that standard contracts containing exoneration clauses have legal consequences for consumers, namely the responsibility that should be borne by business actors becomes the responsibility of consumers. The Consumer Protection Law requires business actors to immediately adjust the standard contracts used with the provisions of the law, but in practice, this is difficult to do.